Comparison of dronedarone vs. flecainide in the maintenance of sinus rhythm, following electrocardioversion in adults with persistent atrial fibrillation: a systematic review and meta-analysis. Issue 5 (10th March 2020) - Wilson, Hannah; Patton, Declan; Moore, Zena; O'Connor, Tom; Nugent, Linda
Abstract: Aims: To compare flecainide and dronedarone for sinus rhythm (SR) maintenance following electrocardioversion of persistent atrial fibrillation (AF), in patients with minimal or no structural heart disease. Methods and results: A systematic search of publications using EMBASE, CENTRAL, CINAHL, and MEDLINE (1989–2019), identified a total of 595 articles. No limitations were applied. Nine articles met the inclusion criteria [five randomized controlled trials (RCTs) and four cohort studies], encompassing 1349 persistent AF candidates. Two retrospective studies compared flecainide with dronedarone, indicating a 6% reduced risk of AF recurrence with flecainide; however, results were not statistically significant [risk ratio (RR) 0.94, 95% confidence interval (CI) 0.71–1.24; P  = 0.66]. One RCT compared dronedarone to placebo, demonstrating a 28% reduced risk of AF recurrence at 6 months (RR 0.72, 95% CI 0.58–0.90; P  = 0.004). Two RCTs compare flecainide to placebo, when a 16% decreased risk of AF recurrence at 6–12 months was indicated; however, these results were not statistically significant (RR 0.84, 95% CI 0.66–1.07; P  = 0.16). Within a 6- to 12-month follow-up period, a combined recurrence rate of AF was examined, in which flecainide and dronedarone maintained SR in 50% and 42%, respectively. Four articles satisfied quality appraisal, one of which focused on flecainide data. Conclusion: Dronedarone and flecainide displayed similar efficacy in maintaining SR in patients following electrocardioversion for persistent AF. The SR maintenance was numerically but not statistically significant in the flecainide group. Side effects uncovered similar pro-arrhythmic activity. However, in light of the deficiency of volume and quality of available evidence, the writer acknowledges the requirement for future research.